Pancakes for supper! - Isaacs, Anne.; Teague, Mark; Bannerman, Helen, 1862-1946. (New York : Scholastic Press, 2006)
In the backwoods of New England, a young girl cleverly fends off the threats of wild animals by trading her clothes for her safety.
Based on The story of Little Black Sambo, by Helen Bannerman.
Keywords: Animals -- Fiction; New England -- Fiction